2020
DOI: 10.1111/febs.15493
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of miR‐15a/16‐1 and miR‐497/195 clusters in immune cell development and homeostasis

Abstract: MicroRNAs (miRNAs) post-transcriptionally repress almost all genes in mammals and thereby form an additional layer of gene regulation. As such, miRNAs impact on nearly every physiological process and have also been associated with cancer. Prominent examples of such miRNAs can be found in the miR-15 family, composed of the bicistronic clusters miR-15a/ 16-1, miR-15b/16-2, and miR-497/195. In particular, the miR-15a/16-1 cluster is deleted in almost two thirds of all chronic B lymphocytic leukemia (CLL) cases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…For instance, Xu et al [1] show that microRNA-520c-3p functions as a novel tumor suppressor in lung adenocarcinoma, and Sun et al [2] propose that microRNA-134 inhibits osteosarcoma angiogenesis and proliferation. Very recent developments have also shown that microRNA clusters can have differential roles in development and homeostasis, as reported by Herzog et al Their conditional and whole-body mouse model deletion of miR-497/195, part of the miR-15 family, did not show onsets of chronic B lymphocytic leukemia or impaired immune cell development, in contrast to mice lacking their miR-15 paralogs [3].…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…For instance, Xu et al [1] show that microRNA-520c-3p functions as a novel tumor suppressor in lung adenocarcinoma, and Sun et al [2] propose that microRNA-134 inhibits osteosarcoma angiogenesis and proliferation. Very recent developments have also shown that microRNA clusters can have differential roles in development and homeostasis, as reported by Herzog et al Their conditional and whole-body mouse model deletion of miR-497/195, part of the miR-15 family, did not show onsets of chronic B lymphocytic leukemia or impaired immune cell development, in contrast to mice lacking their miR-15 paralogs [3].…”
mentioning
confidence: 71%
“…Very recent developments have also shown that microRNA clusters can have differential roles in development and homeostasis, as reported by Herzog et al . Their conditional and whole‐body mouse model deletion of miR‐497/195, part of the miR‐15 family, did not show onsets of chronic B lymphocytic leukemia or impaired immune cell development, in contrast to mice lacking their miR‐15 paralogs [3].…”
mentioning
confidence: 99%
“…To study whether a complete loss of the miR-15 family members expressed in the hematopoietic compartment would affect physiologic immune cell development and function we generated a conditional miR-15a/16-1 miR-15b/16-2 knockout mouse model. We decided to neglect the miR-497/195 cluster in this setting, as it is only marginally expressed in immune cells and was found to be dispensable for the immune system in our previously described miR-497/195 knockout mouse model (Hutter et al 2020). The conditional miR-15a/16-1 and miR-15b/16-2 knockout alleles were generated using CRISPR/Cas9-assisted editing to flank the endogenous clusters with loxP sites in embryonic stem (ES) cells (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The conditional miR-15a/16-1 and miR-15b/16-2 alleles were generated by CRISPR/Cas9-facilitated homologous recombination in murine ES cells, as already described for targeting of the miR-497/195 cluster (Hutter et al 2020). In short, KH2 ES cells ( (Premsrirut et al 2011), C57BL/6 x 129S4/Sv/Jae background, kindly provided by J. Zuber, IMP, Vienna) were electroporated (Nucleofector Kit; Lonza, Switzerland) with two Cas9/sgRNA vectors encoding GFP as a marker and the targeting DNA template containing the miRNA cluster flanked by loxP sites.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation